2020
DOI: 10.1155/2020/7269150
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy and NLRP3 Inflammasome in Liver Fibrosis

Abstract: Liver fibrosis is an intrinsic repair process of chronic injury with excessive deposition of extracellular matrix. As an early stage of various liver diseases, liver fibrosis is a reversible pathological process. Therefore, if not being controlled in time, liver fibrosis will evolve into cirrhosis, liver failure, and liver cancer. It has been demonstrated that hepatic stellate cells (HSCs) play a crucial role in the formation of liver fibrosis. In particular, the activation of HSCs is a key step for li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 72 publications
2
34
1
Order By: Relevance
“…Researchers have identified the characteristics of the NLR family pyrin domain containing 3 (NLRP3) inflammasome belonging to the inflammasome family. NLRP3 inflammasome has three potential activation pathways: (1) ATP signal which occurs outside a cell, leading to potassium efflux and pannexin recruitment; (2) incorporation of crystalized cholesterol, uric acid or amyloid with lysosomal dysfunction after the ingestion and elimination of these particles; and (3) activation by reactive oxygen species (ROS) [ 33 , 35 , 36 ]. Investigations have examined the activation of inflammasome in APAP-induced ALF by a special focus on the contribution of the inflammasome to acute liver disorder [ 37 ].…”
Section: Pathophysiology Of Alfmentioning
confidence: 99%
“…Researchers have identified the characteristics of the NLR family pyrin domain containing 3 (NLRP3) inflammasome belonging to the inflammasome family. NLRP3 inflammasome has three potential activation pathways: (1) ATP signal which occurs outside a cell, leading to potassium efflux and pannexin recruitment; (2) incorporation of crystalized cholesterol, uric acid or amyloid with lysosomal dysfunction after the ingestion and elimination of these particles; and (3) activation by reactive oxygen species (ROS) [ 33 , 35 , 36 ]. Investigations have examined the activation of inflammasome in APAP-induced ALF by a special focus on the contribution of the inflammasome to acute liver disorder [ 37 ].…”
Section: Pathophysiology Of Alfmentioning
confidence: 99%
“…Since exosomes were first discovered in 1983, their molecular mechanisms and functions have been increasingly explored ( Zhang and Yu, 2019 ). It has been reported that exosomes greatly impact cancer progression, cardiovascular disease, liver fibrosis, non-alcoholic steatohepatitis (NASH), and metabolic diseases ( Schroder et al, 2010 ; Wan et al, 20162016 ; Próchnicki and Latz, 2017 ; Moossavi et al, 2018 ; Tai et al, 2018 ; Zhou et al, 2018 ; Tao et al, 2020 ). Currently, there is a growing interest in the association between exosomes and immunoregulation mechanisms in diseases progression has been creeping up ( Sharma and Johnson, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, inflammasomes have been found to include nucleotide-binding domain leucine-rich repeat (NLR) and pyran domain-containing receptor 1 (NLRP1); NLRP3; RIG-I; and caspase recruitment domain containing receptor 4 (NLRC4); and they have been found to be absent in melanoma 2 (AIM2) [ 3 , 4 ]. NLRP3 inflammasome is the most thoroughly studied one at present, and is composed of NLRP3, apoptosis-associated speck-like protein (ASC) and pro-caspase-1 precursor [ 5 , 6 , 7 , 8 , 9 ]. NLRP3, a 115 kDa cytoplasmic protein, contains three domains: one is a leucine-rich repeat (LRR) at the C-end; the second is a central nucleotide-binding and oligomeric domain NACHT with ATPase activity, and the third is a pyran domain (PYD) at the N-end, which is used to recruit ASCs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%